Efficacy of a new video-based training model in spinal surgery - Heiland, Dieter Henrik; Petridis, A. K.; Maslehaty, H.; Thissen, J.; Kinzel, A.; Scholz, M.; Schreiber, L. (Surgical Neurology International, 2014)
Background: An important part of neurosurgical training is the improvement of surgical skills. Acquiring icrosurgical skills follows a learning curve, influenced by specific exercises, feedback, and training. Aim of training should be rapid learning success. The study shows the way in which video-based training can influence he learning curve. Methods: Over a period of 18 months (2011-2012) 12 residents were evaluated in spinal surgery (12 cases per resident) by a skilled evaluator based on different criteria. The evaluation criteria (exposition of important anatomy, intraoperative bleeding, efficacy of using bipolar cauterization) were weighted and added to a single quality-score. The participating residents were divided into two groups. Only one group (n = 5) received video-based training. Results: Residents showed an individually different but explicit increase in microsurgical skills. The quality-score during the first surgery compared with the end point of the study demonstrated a faster improvement of surgical skills in the group with video-based training than in the group without special training. Considering all residents together, the video-training group displayed a steeper gradient of microsurgical success. Comparison of the single resident's microsurgical skills showed individual disparities. Various biases that influence the learning success are under examination. Conclusion: Video-based training can improve microsurgical skills, leading to an improved learning curve. An earlier entry of the learning curve plateau in the video-training group promotes a higher acquisition of surgical skills. Because of the positive effect, we plan to apply the video-based training model to other neurosurgical subspecialties, especially neurovascular and skull base surgery. Copyright: © 2014 Heiland DH.
CRIS-Team Scopus Importer:2024-03-07
Keywords: Learning curve; Microsurgery; Surgical skills; Video-based training